PTU-082 Faecal Incontinence in Inflammatory Bowel Disease: we Don'T ask and they don't Tell. (4th June 2013) - Duncan, J; Sebepos-Rogers, G; Poole-Wilson, O; To, C; Canavan, J B; Kariyawasam, V; Ward, M; Goel, R; Patel, K; Stanton, A; Sastrillo, M; Anderson, S; et al.
Abstract : Introduction: The deleterious effect of faecal incontinence (FI) on quality of life (QOL) is well documented. People with FI experience stigma, embarrassment and social exclusion, and report adverse effects on activities and relationships. Restoration of continence is associated with improvement in QOL. Diarrhoea is associated with increased prevalence of FI and, therefore, people with inflammatory bowel disease (IBD) are at risk. Methods: To investigate how frequently health care professionals (HCPs) assess FI in a cohort of patients with IBD we performed a cross sectional survey of 380 adults attending a tertiary referral IBD clinic. Patient surveys were: the validated ICIQ-B questionnaire, detailing frequency and severity of bowel pattern, control and quality of life; and the non-validated Bowel Leakage Questionnaire, detailing any prior interventions by health care professionals. Demographics of age, gender, diagnosis, Montreal classification, St Mark's Continence Score and disease activity were also recorded. Data was entered into a database and analysed using SPSS statistical package. Results: 229/380 (60%) had Crohn's Disease (CD) and 180/380 (47%) were female. Median age was 38 years (IQR:31–50) with a median disease duration of 8.7 years (3.4–15.1). 343/380 (90%) had experienced incontinence of flatus or faeces while 255/380 (67%) reported FI. Only 136/380 (36%) had been asked about FI during an encounter with a HCP. Of the people who had been asked about FI, the vast majority had been asked in IBD clinics (130/136, 96%). Fewer enquiries were made by HCPs in a primary care setting with 42/136 (31%) people having been asked by a family doctor and 12/136 (9%) by a practise nurse. A minority of patients spontaneously volunteered information about incontinence to a healthcare professional (146/380, 39%). Of the people who had discussed continence issues with a HCP, 55 (38%) were offered specific advice or referral for treatment. Those who volunteered information regarding continence had worse ICIQ-B control scores (9 (6–14) vs 3 (1–8), p < 0.0001)) and quality of life scores (16 (11–20) vs 9 [6–14], p < 0.0001), reflecting greater burden of disease. Conclusion: Faecal incontinence is common in IBD. It is both under-reported by patients and under-recognised by healthcare professionals. Because symptoms and QOL can be significantly improved with appropriate intervention, HCPs need to enquire about FI as part of routine assessment. Disclosure of Interest: None Declared